Primary Vasculitis in Childhood: GPA and MPA in Childhood - Jariwala, Mehul P.; Laxer, Ronald M. (Frontiers in Pediatrics, 2018)
Childhood onset anti-neutrophilic cytoplasmic antibody (ANCA) associated vasculitis (AAV) is a rare group of primary systemic vasculitides affecting medium and small blood vessels. AAV includes granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), eosinophilic granulomatosis with polyangiitis (EGPA) and renal limited ANCA vasculitis. These disorders are associated with severe clinical manifestations, frequent relapses and a high cumulative morbidity, and often present with multisystem involvement. Renal involvement is common in the pediatric age group, characterized by pauci-immune necrotizing and crescentic glomerulonephritis which frequently progresses to chronic kidney disease in adulthood. ANCAs against proteinase 3 (PR3-ANCA) or myeloperoxidase (MPO) (MPO-ANCA) remain the hallmark of AAV and are integral to the disease pathogenesis. Newer understanding of neutrophil extracellular traps and complement activation have provided better insights into disease pathogenesis. A pediatric vasculitis working group has developed and validated childhood vasculitis classification criteria and disease activity and damage scores. No specific pediatric treatment recommendations exist due to rare nature of the illness in pediatric population. Smaller case series have been published on the efficacy of adult treatment regimens in pediatric patients. The prognosis often remains guarded with frequent relapses and a high cumulative morbidity. The aim of this article is to provide a comprehensive review on pediatric AAV with a focus on recent observations regarding epidemiology, disease pathogenesis, treatment and prognosis.